Local Agricultural Products Strategy to Improve Resilience in a New Adaptation Era - I Gusti Ayu Purnamawati; Gede Adi Yuniarta; Elly Herliyani (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
The resilience of the community in the face of the Covid-19 pandemic led the government to disburse funds to help the economy grow again. Amid public concern, the agricultural sector is the most important alternative to survive. This research tries to analyze local product development strategies to survive the downturn in the era of adaptation to new habits, especially agricultural businesses. The approach used is quantitative. The subjects in this study were the Bali Provincial Industry and Trade Office, agribusiness managers in Buleleng Regency, Bali Province, and consumers who buy these agricultural products. The development strategy uses SWOT analysis. The weighting of the four influential variables is the product strategy, competitive strategy, partnership, and technology using the analytical hierarchical process approach. The application of a strategy for growth and stability in the agricultural sector through the empowerment of rural communities can improve the resilience.